2011
DOI: 10.1152/ajpheart.01026.2010
|View full text |Cite
|
Sign up to set email alerts
|

Narrowing a region on rat chromosome 13 that protects against hypertension in Dahl SS-13BNcongenic strains

Abstract: RJ. Narrowing a region on rat chromosome 13 that protects against hypertension in Dahl SS-13 BN congenic strains. Am J Physiol Heart Circ Physiol 300: H1530 -H1535, 2011. First published January 21, 2011 doi:10.1152/ajpheart.01026.2010.-Transfer of chromosome 13 from the Brown Norway (BN) rat onto the Dahl saltsensitive (SS) genetic background attenuates the development of hypertension, but the genes involved remain to be identified. The purpose of the present study was to confirm by telemetry that a congenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 22 publications
3
18
0
Order By: Relevance
“…Study of the role and gene composition of identified quantitative trait loci followed, through the creation of consomic or congenic strains in which putative causative or protective chromosomes or chromosome regions were introgressed from a control to an SS strain or vice versa. With the Dahl-SS strain used as the genetic background, consomic strains harboring chromosome 9 from the Dahl-SR strain 95 ; chromosomes 13, 96 12, 97 104 or chromosomes 15 and 20 of the Brown Norway into the Fawn Hooded rat with salt-induced hypertension. 105 Many of these observations detected sexual dimorphism in the chromosomal effects, and some characterized the mechanism for the antihypertensive effect of protective introgressed chromosomal segments (eg, the segment of chromosome 2 of the Brown Norway strain that improves SS hypertension in Dahl SS reduces inflammation and shifts the balance between CD4 + and regulatory T cells 106 ).…”
Section: Genetics and Ss Phenotype In Rodentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study of the role and gene composition of identified quantitative trait loci followed, through the creation of consomic or congenic strains in which putative causative or protective chromosomes or chromosome regions were introgressed from a control to an SS strain or vice versa. With the Dahl-SS strain used as the genetic background, consomic strains harboring chromosome 9 from the Dahl-SR strain 95 ; chromosomes 13, 96 12, 97 104 or chromosomes 15 and 20 of the Brown Norway into the Fawn Hooded rat with salt-induced hypertension. 105 Many of these observations detected sexual dimorphism in the chromosomal effects, and some characterized the mechanism for the antihypertensive effect of protective introgressed chromosomal segments (eg, the segment of chromosome 2 of the Brown Norway strain that improves SS hypertension in Dahl SS reduces inflammation and shifts the balance between CD4 + and regulatory T cells 106 ).…”
Section: Genetics and Ss Phenotype In Rodentsmentioning
confidence: 99%
“…108 A role for narrower DNA segments was investigated by the creation of congenic strains with introgressed overlapping regions of these chromosomes. A combination of these experiments and the study of differential expression of genes between the congenic and parental strains, detection of nonsynonymous single nucleotide polymorphisms in the regions of interest, and transcriptomic analysis has revealed a number of possible candidate genes, 96,97,100,101,109,110 the majority of which have no previously known cardiovascular regulatory function. However, even with high-resolution substitution mapping, there are usually additional variants flanking a substituted candidate gene, requiring genetic engineering to sort out the significance of the finding.…”
Section: Genetics and Ss Phenotype In Rodentsmentioning
confidence: 99%
“…52 Briefly, 13-week-old rats were anesthetized with 2% isoflurane, and a BP transmitter (PA-C40, DSI) was implanted subcutaneously with the catheter tip secured in the abdominal aorta via the femoral artery. After the 3-day recovery period, BP was measured by radio telemetry in conscious freely moving animals for 3 days, for 3 hours per day.…”
Section: Bp Measurementsmentioning
confidence: 99%
“…72 In further subcongenic breeding experiments, the QTL linked to proteinuria development on RNO13 was narrowed to a 1.9-Mb region, which however also affected BP (Table 3). 73 …”
Section: Buffalo Rat Strain Breedingmentioning
confidence: 99%